Feature matching algorithm based on partial limitation search region - Zhang Zhenning (Dianzi Jishu Yingyong, 2018)
This paper proposes a feature matching algorithm for partial limitation search regions, which combines spatial constraints with local descriptors. Based on the ASIFT algorithm, this paper improves the defects of directly removing one-to-many and many-to-one feature points in the feature matching phase. Since many of these removed feature points can be properly matched,resulting match points less. This paper will find a new unmatched pair of points within the surrounding area of the matching pairs, and finally achieve the goal of raising the correct number of matches. Experiments show that the feature matching algorithm proposed in this paper can greatly increase the number of feature matching compared with the ASIFT algorithm.